2021
DOI: 10.1093/icc/dtab031
|View full text |Cite
|
Sign up to set email alerts
|

The rise in inequality after pandemics: can fiscal support play a mitigating role?

Abstract: Major epidemics of the last two decades (SARS, H1N1, MERS, Ebola, and Zika) have been followed by increases in inequality [Furceri et al. (2020), COVID Economics, 12, 138–157]. In this article, we show that the extent of fiscal consolidation in the years following the onset of these pandemics has played an important role in determining the extent of the increase in inequality. Episodes marked by extreme austerity—measured using either the government’s fiscal balance, health expenditures, or redistribution—have… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…13 However, as argued by Furceri et al. ( 2021 ), the observed cushioning effect of policy measures might not be long-lasting. As they have shown, the rise in inequality following after major epidemics over the last two decades (SARS, H1N1, MERS, Ebola and Zika) has been higher in episodes of greater austerity.…”
Section: Discussionmentioning
confidence: 95%
“…13 However, as argued by Furceri et al. ( 2021 ), the observed cushioning effect of policy measures might not be long-lasting. As they have shown, the rise in inequality following after major epidemics over the last two decades (SARS, H1N1, MERS, Ebola and Zika) has been higher in episodes of greater austerity.…”
Section: Discussionmentioning
confidence: 95%
“…The negative sign of the coefficient regarding the change of structural general government balance may also have another interpretation. Furceri et al ( 2021 ) showed, using previous episodes of other pandemics that if fiscal response is strongly supportive, inequality barely increases in the aftermath of pandemics. On the other hand, austerity leads to a significant increase in inequality.…”
Section: Resultsmentioning
confidence: 99%
“…She also shows that significant substitution effects between consumption categories are observed. Furceri et al ( 2021 ) focus on the distributional consequences of major pandemics in the past two decades and show that they led to increases in the Gini coefficients and a greater income share amongst higher-income deciles. Krueger et al ( 2020 ) combine a macroeconomic model with an epidemiological model estimated on Swedish health data.…”
Section: Introductionmentioning
confidence: 99%
“…Gechert et al (2021b) show this feature consistently for macro and micro data from Germany. Furceri et al (2021) point out that pandemics require persistent government support of low incomes in order to prevent inequality that typically follows after pandemic-induced austerity.…”
Section: Fiscal Policymentioning
confidence: 99%